2008
DOI: 10.1038/sj.tpj.6500491
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the SLC6A4 and HTR2A genes influence treatment outcome following antidepressant therapy

Abstract: The majority of antidepressant drugs act by increasing synaptic serotonin levels in the brain. Genetic variation in serotonin-related genes may therefore influence antidepressant efficacy. In this study, nine polymorphisms in four serotonin receptor genes (HTR1B, HTR2A, HTR5A and HTR6) and the serotonin transporter gene (SLC6A4) were analysed to investigate their influence on antidepressant response in a well-characterized unipolar depressive population (n ¼ 166) following a protocolized treatment regimen. 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 39 publications
1
75
2
3
Order By: Relevance
“…163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes. 83,[187][188][189][190][191] Interestingly, Lotrich and colleagues 192 recently reported that paroxetine blood concentration was positively associated with HAM-D response in a sample of elderly patients, but this association was found to be significant only in carriers of the short allele.…”
Section: Comtmentioning
confidence: 95%
See 1 more Smart Citation
“…163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes. 83,[187][188][189][190][191] Interestingly, Lotrich and colleagues 192 recently reported that paroxetine blood concentration was positively associated with HAM-D response in a sample of elderly patients, but this association was found to be significant only in carriers of the short allele.…”
Section: Comtmentioning
confidence: 95%
“…259 Several other variants have been reported to predict antidepressant response. 85,117,134,179,229,260,261 Table 8 lists relevant genetic association studies that investigated the impact of these variations on the antidepressant response.…”
Section: Serotonin 2amentioning
confidence: 99%
“…Despite preliminary negative results [102], a subsequent study reported that C/T carriers showed better AD response [103]. Nevertheless, this finding was not replicated by further studies [82,104].…”
Section: Serotonin Receptorsmentioning
confidence: 56%
“…Another polymorphism influencing SERT expression, described as 17bp VNTR polymorphism, was identified within intron 2 (STin2) [80]. Several studies reported an influence of STin2 on response to ADs, but other investigations were not able to repeat these findings [81][82][83][84][85]. Moreover, it was proposed that STin2 10/12 genotype may be associated with poorer antidepressant effect, especially in Asian populations [86].…”
Section: Serotonin Transporter (Slc6a4)mentioning
confidence: 95%
“…[1][2][3][4] Therefore, it is possible that the therapeutic action of antidepressants is initiated by gene expression changes in the early stages of treatment and antidepressant pharmacogenomic studies may provide a means to uncover candidate genes relevant to antidepressant response. Indeed, genes such as ABCB1, BDNF, SLC6A4 and TPH1, which have been associated with antidepressant response, [5][6][7][8] show acute antidepressant-induced expression changes. [9][10][11][12] RN46A cells are committed to a neuronal lineage and express the serotonin transporter (Slc6a4), 13 the pharmacological target of selective serotonin reuptake inhibitors (SSRIs).…”
Section: Introductionmentioning
confidence: 99%